Outbreak of Tinea capitis and corporis in a primary school in Antananarivo, Madagascar - Carod, Jean-François; Ratsitorahina, Mahery; Raherimandimby, Hasina; Hincky Vitrat, Virginie; Ravaolimalala Andrianaja, Vololomboahangy; Contet-Audonneau, Nelly (The Journal of Infection in Developing Countries, 2011)
Introduction: Tinea capitis is common among schoolchildren in developing countries but underreported in Madagascar. We report the occurrence of an outbreak of gray patch tinea capitis due to Microsporum langeronii in a public primary school of Antananarivo, the capital city of Madagascar. Methodology: Forty-two children were included, 27 (64%) of them presenting with tinea capitis and 32 (76%) with Tinea corporis. Patients were treated with griseofulvin 500 mg and Povidone-iodine 4% and followed up for four weeks. Results: Twenty-five (93%) of the 27 children with tinea capitis presented a gray patch as the main clinical feature. All these cases were fluorescent under Wood's UV light and positive in cultures for M. langeronii. All 27 children reported a contact with infected classmates, and 19 (70%) reported to have infected brothers and sisters at home. After four weeks of treatment, all patients recovered. Conclusion: Appropriate treatment and improved hygienic practices reduced the occurrence of tinea in the studied school and no more cases of tinea capitis or corporis occurred after the outbreak.